TWO SUMMATION FORMULAE RELATING HYPERGEOMETRIC FUNCTION (Global Journal of Science Frontier Research, 2012)
The aim of the present paper is to obtain two summation formulae associated to Hypergeometric function.The results derived in this paper are of general character and are believed to be new.
Keywords: Contiguous relation; Recurrence relation; Gauss second summation theorem